Perlindungan Hukum Jasa Kurir Jual Beli Online dalam Sistem Layanan Cash on Delivery - Frengky Petra Beti; Jimmy Pello; Darius A. Kian (Hakim, 2024)
The issue of online shopping with the COD service is closely related to consumers' desire to avoid fraud in online transactions. Consequently, consumers always wish to inspect their ordered items before making payment, even though COD terms prohibit buyers from opening orders before payment. This situation leads to various problems, such as buyers making complaints to couriers using unlawful methods like threats, insults, extortion, and the like. These actions are directed towards couriers who are unaware of the regulations governing online shopping transactions between buyers and sellers. In some cases, social media reports often express these complaints by attacking couriers personally, ranging from insults to threats involving sharp weapons. This research aims to understand and analyze the criminal law regulations that provide legal protection for courier services. Additionally, it seeks to identify efforts that can be undertaken by service provider companies to protect couriers in online buying and selling. The research adopts a normative legal research method, which examines, maintains, and develops positive legal structures using legal logic. It will also refer to existing legal materials such as legal principles, legal doctrines, regulations, and legal literature, as well as legal theories. The study focuses on addressing normative gaps in regulations that govern the protection of couriers as employees in courier service companies. An employee is defined as anyone who works and receives wages or compensation in another form. In the agreement mutually accepted, the position of a courier is established as a partner of the courier service provider/expedition company. Conducting pre-delivery checks on the condition of goods helps reduce disputes related to damage or loss. Furthermore, it is crucial to understand and recognize the rights and obligations of couriers in the cooperation agreement, especially concerning COD payments, as it is a critical aspect. Legal protection for couriers needs to be considered and possibly codified to cover specific aspects that can provide security and assurance for their rights.